2013
DOI: 10.1371/journal.pone.0052680
|View full text |Cite|
|
Sign up to set email alerts
|

IRC-082451, a Novel Multitargeting Molecule, Reduces L-DOPA-Induced Dyskinesias in MPTP Parkinsonian Primates

Abstract: The development of dyskinesias following chronic L-DOPA replacement therapy remains a major problem in the long-term treatment of Parkinson’s disease. This study aimed at evaluating the effect of IRC-082451 (base of BN82451), a novel multitargeting hybrid molecule, on L-DOPA-induced dyskinesias (LIDs) and hypolocomotor activity in a non-human primate model of PD. IRC-082451 displays multiple properties: it inhibits neuronal excitotoxicity (sodium channel blocker), oxidative stress (antioxidant) and neuroinflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Recently, non-neuronal factor such as inflammation have been suggested to be involved in L-DOPA-induced dyskinesia [36,46]. The anti-dyskinetic effects of anti-inflammatory treatments with either corticosterone [46] or IRC-82451 (a multitargeting molecule [47]) support the hypothesis. Moreover, there is evidence of an increased expression of inflammatory markers in vivo in human Parkinson's disease patients [4] and in animal models [36,48,49].…”
Section: Introductionmentioning
confidence: 87%
“…Recently, non-neuronal factor such as inflammation have been suggested to be involved in L-DOPA-induced dyskinesia [36,46]. The anti-dyskinetic effects of anti-inflammatory treatments with either corticosterone [46] or IRC-82451 (a multitargeting molecule [47]) support the hypothesis. Moreover, there is evidence of an increased expression of inflammatory markers in vivo in human Parkinson's disease patients [4] and in animal models [36,48,49].…”
Section: Introductionmentioning
confidence: 87%
“…However, there is limited understanding of the role of the immune system in the generation of LID likely to be due to the lack of an appropriate animal model. The only clinically available treatment for LID, amantadine has been shown to have anti-inflammatory properties (Ossola et al, 2011 ) and other approaches have found that molecules with anti-inflammatory activity may help reduce LID severity or onset (Barnum et al, 2008 ; Aron Badin et al, 2013 ; Bortolanza et al, 2015 ). Importantly in the context of striatal plasticity anti-inflammatories have been shown to improve spine abnormalities in mouse models of Huntington’s disease, a link that may be worth further investigation (Simmons et al, 2013 ).…”
Section: Inflammation and Dyskinesiamentioning
confidence: 99%
“…In trials of acute coadministration with l ‐dopa, MR1916 hydrobromide (Mochida Pharmaceuticals, Gotemba, Japan) was dissolved in dimethyl sulfoxide and cremophor, and injected subcutaneously at 4 escalating doses (0.0015, 0.005, 0.015, and 0.05 mg/kg). In these trials, amantadine hydrochloride (Sigma‐Aldrich) was dissolved in saline and injected subcutaneously at 2 doses (5 and 10 mg/kg) . In each acute trial (optimal and suboptimal l ‐dopa dose), a vehicle injection (MR1916 at 0 mg/kg) was included as control.…”
Section: Methodsmentioning
confidence: 99%